Spontaneous Rupture of the Kidney Due to Acute Lymphoblastic Leukemia: The First Episode and a Glance on the Literature - Taha, Sami Mahjoub; Abd El Geyoom, Awad Al Kareem; E, Mohammed; Ahmed, Imam M; Osman, Nada; Taha, Musab Mahjoub (Global Journal of Medical and Clinical Case Reports, 2018)
Spontaneous rupture of the kidney consists of the atraumatic disruption of the renal parenchyma, followed by hemorrhage or leakage of urine into the perinephric space. A17 years old male known case of Acute Lymphoblastic Leukemia (ALL), referred to the urology department with right loin pain and fever for 3days. There was no history of trauma. Investigations revealed low hemoglobin, low platelets 18000 and urine analysis showed pus cells 14-18 cell/HPF and RBCs 2-4 /HPF. Renal functions tests and coagulation profile were normal. CT urography showed bulky right kidney with mid pole laceration leaking of the contrast in the perinephric space. Conservative treatment was done (Double j insertion-ultrasound guided aspiration). Postoperatively he was generally well, afebrile, pain subside and repeated abdominal U/S showed no collection. Conservative management can be appropriate where clinical signs stabilize.